The influence of the width of crack opening in reinforced concrete structures on the technology of their repair - Molodid О.; Plokhuta, R. (Ways to Improve Construction Efficiency, 2019)
The most frequent damages of concrete and reinforced concrete structures are cracks. According to DSTU B V.3.1-2: 2016, for their repair, solutions based on cement, Portland cement, thermosetting resins and thermoplastic polymers are used by injection and impregnation. The article presents the results of experimental studies to establish the influence of the width of crack opening of reinforced concrete structures on the technology of their injection with composite fluid. It was established that for cracks with the width of the opening up to 0.25 mm and for impregnating the body of the concrete to a depth of up to 2-3 mm, the effective composite liquid "Consolid 1" and the system "lotochok". For gluing cracks from 0.3 mm to 0.7 mm, the «Edmok Injection» composite liquid is effective. For gluing cracks with a opening width of 0.7 mm, the technology of impregnation of the structure with a composite liquid “Consolid 1” using the “lotochok” system and injection of cracks with the “Edmok injection” composite liquid 24 hours after impregnation is effective.